Free availability of high‐energy foods led to energy over‐ingestion and protein under‐ingestion in choice‐fed broilers. (22nd May 2015) - Catanese, Francisco; Rodriguez Ganduglia, Héctor; Villalba, Juan J.; Distel, Roberto A.
Abstract: The objective of this study was to compare energy and protein content of the diet selected by choice‐fed broilers with that of broilers fed a balanced diet. One hundred and eighty 1‐day‐old male broilers were randomly assigned in groups of 10 to one of three experimental treatments ( n  = 6). Control broilers were fed a standard balanced diet, whereas choice‐fed broilers were fed three foods which were more concentrated (Choice C+ treatment) or less concentrated (Choice C– treatment) in protein, carbohydrate or fat. We evaluated food intake behavior, nutrient intake, and performance parameters of broilers from 2 to 7 weeks of age. Choice C+ broilers showed enhanced preference for the high‐fat food, which led to higher energy intake and lower protein intake than those of control broilers at 2 to 4 weeks of age. Body weight, weight gain and feed conversion efficiency were negatively affected by diet selection of Choice C+ broilers. Choice C– broilers selected a balanced diet, and showed performance parameters similar to those of control broilers. Our results supported the hypothesis that free availability of high‐energy foods bias ingestive behavior of choice‐fed broilers toward selecting a diet with higher energy and lower protein than needed for normal growth.